Psychological Predictors for Depression and Burnout Among German Junior Elite Athletes - Nixdorf, Insa; Beckmann, Jürgen; Nixdorf, Raphael (Frontiers in Psychology, 2020)
There exists a strong need for research in clinical sport psychology which does not merely gather information on prevalence rates for psychological disorders and case studies of affected athletes. Rather, research should also uncover the underlying psychological variables which increase the risk for depression and burnout in elite athletes. Many studies gather general factors (e.g. gender, injury, sport discipline) and stay on a more descriptive level. Both constructs (burnout and depression) are based on a temporal, stress-related process model assuming the development of either syndrome results from unfavorable personal (e.g. dysfunctional attitudes, perfectionism, negative coping strategies) or environmental (e.g. cohesion) factors coexisting with severe stressors (i.e. chronic stress). Integrating this knowledge, we propose a shared model for depression and burnout in athletes: a sport specific diathesis-stress model. The present longitudinal study assesses data throughout one sporting season to analyze predictors for both constructs in junior elite athletes. Hierarchical multiple linear regression analyses resulted in six predictors for best model fit. The following factors demonstrated a significant impact on predicting (a) burnout or (b) depression scores at the end of the season: dysfunctional attitudes (a and b), coping strategies (a and b), perfectionism (a), recovery (b), stress (a) and the level of depression at onset (b). Variables such as cohesion or attributional style did not significantly predict depression or burnout. The study supports the structure of a process model (diathesis-stress model) for burnout and depression with the assumption of temporal progression. With some vulnerabilities and their temporal, developmental link identified, prevention can become athlete-specific, effective and economical.